The influence of two photobiomodulation protocols on orthodontically induced inflammatory root resorption (a randomized controlled clinical trial) - Farah Y. Eid; Walid A. El-Kenany; Mohamed I. Mowafy; Ahmed R. El-Kalza (BMC, 2022)
Abstract Background Controversial results have been reported regarding the impact of photobiomodulation (PBM) on orthodontically induced inflammatory root resorption (OIIRR). The aim of this study was to evaluate the influence of two PBM protocols, one of them requiring a high application frequency (on days 0, 3, 7, 14, then every 2 weeks), while the second requires less frequent applications (every 3 weeks), on OIIRR accompanying orthodontic treatment. Methods Twenty female patients were recruited for this randomized controlled trial, requiring the therapeutic extraction of maxillary first premolars, and they were randomly divided into 2 equal groups. In Group A, one side of the maxillary arch randomly received PBM on days 0, 3, 7, 14, and every 2 weeks thereafter, while in Group B, one side was randomly chosen to receive PBM every 3 weeks. The laser applied was a Diode laser with a wavelength of 980 nm, in a continuous mode. Canine retraction in both groups was carried out using closed-coil springs, delivering 150 g of force, and the force level was checked every 3 weeks, over a 12-week study period. Pre-retraction and post-retraction cone-beam computed tomography (CBCT) was done for the evaluation of OIIRR. Results No significant differences in the amount of OIIRR have been reported between the laser and control sides in both groups A and B. Also, no significant differences have been reported between the laser sides in both groups. Conclusions Photobiomodulation does not affect OIIRR, whether by increasing or decreasing its occurrence, with both laser application protocols. Therefore, it can be stated that PBM does not result in root resorption less than the commonly observed range elicited with conventional orthodontic treatment, and that it has no effect on OIIRR. Trial registration Two Low-level Laser Irradiation Protocols on the Rate of Canine Retraction (NCT04926389), 15/06/2021-retrospectively registered. https://clinicaltrials.gov/ct2/show/NCT04926389 .